2013
DOI: 10.1159/000362437
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Analysis of Severe Neutropenia in Patients Receiving Concomitant Administration of Docetaxel and Clarithromycin

Abstract: Background: Neutropenia is one of the most important dose-limiting toxicities of docetaxel. Docetaxel is metabolized by cytochrome P450 3A4 (CYP3A4). Clarithromycin, a potent inhibitor of CYP3A4, is occasionally used in combination with docetaxel. The aim of this study was to evaluate whether the risk of severe neutropenia induced by docetaxel was increased by concomitant administration of clarithromycin. Methods: Patients with advanced lung cancer receiving docetaxel were identified from an electronic medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Several factors, such as female gender, [ 15 17 ] younger age, [ 18 20 ] lower BMI, [ 21 , 22 ] and lower pretreatment blood cell counts, [ 17 , 23 , 24 ] and hemoglobin levels, [ 19 , 25 27 ] were identified as risk factors for severe CIN and/or febrile neutropenia. However, a pharmacogenetic approach based solely on polymorphisms involved in antitumor agent activity appears to be insufficient.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors, such as female gender, [ 15 17 ] younger age, [ 18 20 ] lower BMI, [ 21 , 22 ] and lower pretreatment blood cell counts, [ 17 , 23 , 24 ] and hemoglobin levels, [ 19 , 25 27 ] were identified as risk factors for severe CIN and/or febrile neutropenia. However, a pharmacogenetic approach based solely on polymorphisms involved in antitumor agent activity appears to be insufficient.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms by which the systemic inflammatory response is involved in chemotherapy-related toxicities could be partially attributed to an alteration of the principal drug-metabolizing enzyme of chemotherapeutic agents, such as P450 3A cytochrome [31]. It has been reported that the activity of cytochrome P450 3A is compromised in cancer patients with an elevated CRP concentration [32].…”
Section: Discussionmentioning
confidence: 99%
“…Cabazitaxel and docetaxel are metabolized mainly by CYP3A4 [2, 3], so concomitant use of either of these agents with a drug that affects CYP3A4 activity requires caution. Concomitant use of clarithromycin, which inhibits CYP3A4, with docetaxel has been reported to increase the plasma concentration of docetaxel and the risk of neutropenia [4]. Moreover, coadministration of ketoconazole, another strong CYP3A4 inhibitor, with cabazitaxel was reported to increase the area under the curve of cabazitaxel by around 25% [5].…”
Section: Introductionmentioning
confidence: 99%